2004
DOI: 10.1002/jobm.200310366
|View full text |Cite
|
Sign up to set email alerts
|

Screening of filamentous fungi for the decolorization of a commercial reactive dye

Abstract: The aim of this work is to verify the ability of 19 isolates of 13 different fungal species to decolorize the reactive dye blue-BF-R. The isolates of Pleurotus pulmonarius, P. ostreatus, P. ëous, P. citrinopileatus, Lentinus edodes, Phanerochaete chrysosporium, Schizophyllum commune, Agaricus blazei, Ganoderma sp. and four isolates obtained from textile effluent were evaluated in minimum liquid medium. In addition, seven of them were also evaluated on solid medium, and both media were both added 0.5 g dye/l. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…This remarkable decrease in the dye decolorization on the eighth day is probably due to the formation of metabolites, and this decreasing trend continued until the tenth day. Different fungi have different decolorization potential on chemically different dyes, and screening for ligninolytic fungi for dye decolorization must be conducted under conditions as similar as possible [9,20,21]. The first sign of fungal mycelia growth was seen 24 h after inoculation, and that medium was completely decolorized by Lentinula edodes within 6 days [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This remarkable decrease in the dye decolorization on the eighth day is probably due to the formation of metabolites, and this decreasing trend continued until the tenth day. Different fungi have different decolorization potential on chemically different dyes, and screening for ligninolytic fungi for dye decolorization must be conducted under conditions as similar as possible [9,20,21]. The first sign of fungal mycelia growth was seen 24 h after inoculation, and that medium was completely decolorized by Lentinula edodes within 6 days [11].…”
Section: Resultsmentioning
confidence: 99%
“…Although decolorization is a challenging process to the textile industry, the great potential of microbial decolorizing can be adopted as an effective tool. In the recent past, there has been an intensive research on bioremediation of dyes, and the use of ligninolytic fungi is turning into a promising alternative to replace or supplement present treatment processes [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…They originate from basidiocarps isolated from different Brazilian ecosystems, including tropical forests. Earlier studies have identified Brazilian strains able to degrade different textile dyes (Okino et al 2001;Balan and Monteiro 2001;Dos Santos et al 2004;Machado et al 2005;. In these studies-as well as in most other studies evaluating the capacity of basidiomycetes to degrade textile dye-stuffs-the authors employed culture conditions proper to the development of fungi.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, in recent years, there have been intensive researches on fungal decolorization of textile wastewater. The use of fungi is a promising alternative to replace or supplement current treatments (8,13,18).…”
mentioning
confidence: 99%
“…Several fungi are capable of mineralizing pollutant compounds through their highly oxidative and non-specific ligninolytic enzymes, which are also responsible for the decolorization and degradation of many different dyes (13).…”
mentioning
confidence: 99%